Case 3832: Cryphalus saltuarius Weise, 1891 (Coleoptera, Curculionidae): proposed conservation of the specific name by suppression of Bostrichus asperatus Gyllanhal, 1813 (currently Cryphalus asperatus) (Bulletin of Zoological Nomenclature)
Noticed in BZN 77: 113 on 30 December 2020.